Integrated Islamic School Competitiveness Management - Faruuq Trifauzi; Tobroni Tobroni; Muhammad In'am Esha (Al-Hayat: Journal of Islamic Education, 2022)
Education is a service product produced by non-profit educational institutions so that the educational process results are visible. To learn more about education marketing, you must first know the substance and characteristics of services and marketing concepts so that the application of education marketing is in the correct position by the values and nature of education itself. Therefore, this study aims to find marketing management concepts for private Islamic educational institutions competitive at LPI Al-Badar Tulungagung. This research uses a qualitative approach with a multi-case study type. Data were obtained from the results of interviews, observations, and documentation. The data analysis is carried out since the researcher will come to the research object. After the data collection process, the study is carried out through data condensation, data presentation, and conclusion. The method of credibility, dependability, confirmability and transferability is used to check the validity of the data as well as possible. The findings of this study are the preparation of the concept, program selection, target market and quality of alums. In this way, a concept is formed; the concept of habituation, the concept of mental education, the concept of coordination and confirmation management and the concept of personal branding.